Sistem Aplikasi Logika Fuzzy Untuk Penentuan Harga Produksi Furniture Menggunakan Metode Sugeno - Yusra Ramza; Alwendi (Prosiding Seminar Nasional Teknoka, 2020)
The survival of a company is very important to maintain company productivity. The specific strategy used by a company to set the price of an item departs from a marketing strategy that is formulated to achieve its own goals. Therefore, the company needs to calculate the cost of goods because it is very important for the company's financial reporting. This study aims to allocate the cost of production of furniture for one product. The method used is the Fuzzy Sugeno method which is implemented in the MATLAB language. The application of the Fuzzy Sugeno inference method to determine the production price is based on the cost of raw materials and overhead costs. Data were analyzed using Fuzzy Sugeno inference, which produces output in the form of constants and linear equations. Based on tests carried out using the MATLAB application, it can be seen that the Fuzzy Sugeno inference technique provides the expected response, which can be used to calculate the cost of goods manufactured from a single product.